History as fantasy in music, sound, image and media - Cook, James (Musicologist); Kolassa, Alexander; Robinson, Alexander; Whittaker, Adam (New York, NY : Routledge, 2024)
"Exploring how music is used to portray the past in a variety of media, this book probes the relationship between history and fantasy in the imagination of the musical past. The volume brings together essays from multidisciplinary perspectives, addressing the use of music to convey a sense of the past in a wide range of multimedia contexts, including television, documentaries, opera, musical theatre, contemporary and historical film, video games, and virtual reality. With a focus on early music and medievalism, the contributors theorise the role of music and sound in constructing ideas of the past. In three interrelated sections, the chapters problematise notions of historical authenticity on the stage and screen; theorise the future of musical histories in immersive and virtual media; and explore sound's role in more fantastical appropriations of history in television and video games. Together, they pose provocative questions regarding our perceptions of 'early' music and the sensory experience of distant history. Offering new ways to understand the past at the crossroads of musical and visual culture, this collection is relevant to researchers across music, media, historical and cultural studies"--
Introduction. Beyond Authenticity in Music, History and Fantasy / James Cook, Alexander Kolassa, Alexander Robinson, Adam Whittaker -- I. Using and Misusing Early Music. 'Official' (Televisual) History, Music, and the Reinforcement of Popular Imagination : the Case of David Starkey's Monarchy (2004-2006) / Alexander Robinson ; Damon Albarn, Dr Dee, and situation specific medievalism : An ephemeral fantasy or a disposable commodity? / Ralph Corrigan ; Shakespeare, the Early Modern, and Period Song in the American Silent Cinema / Kendra Preston Leonard ; Early Music in the 'Early Game' / Jennifer Smith ; A Masked Ritual and Backwards Priests : Aural and Visual Corruption in Stanley Kubrick's Eyes Wide Shut / Daniel Trocmé-Latter -- II. Early music, immersive media, and virtual histories. Audio-Visual Interaction in Virtual Worlds : Seeing Sound and Hearing Objects in Visual Cultures / James Cook ; Half-real worlds? Immersion and the representation of musical pasts in virtual reality / Adam Whittaker ; Authenticity in Sound Design for Virtual Reality / Stephen Tatlow -- III. Early music out of time and space. Haunted by the Past : Music and Folk Horror in Children of the Stones ; Pixels et al. : Multi-layered Representation of Past(s) in the Audio, Visual and Ludic Elements of Shovel Knight and Other Screen Media / Dean Chalmers ; The Endless Knot : Turning the Seasons in Harrison Birtwistle's Gawain (1991) and David Lowery's The Green Knight (2021) / George K. Haggett ; A Jolly Good Thirteenth-Century Romp : Galavant, Architextuality and the Intertextual Performance of Race, Gender, and Social Class in a Medievalist Musical Comedy for Television / William A. Everett.
Keywords: Music and history; History in motion pictures; Middle Ages in motion pictures; Motion picture music -- History and criticism; Television music -- History and criticism; Music -- 500-1400 -- History and criticism; Music -- 15th century -- History and criticism; Music -- 16th century -- History and criticism; History in popular culture; Sound in virtual reality; Medievalism; History in opera; MUSIC / General; MUSIC / History & Criticism; PERFORMING ARTS / Film & Video / History & Criticism